The influence of education by using 5J pregnancy nutrition guidebook for the prevention of fetal growth restriction and maternal nutritional sufficiency - Fonda Octarianingsih Shariff; Kevin Andhara Setya Prameswari; Imelda Carolia (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Stunting is a growth and development disorder experienced by children due to poor nutrition, recurring infections, and inadequate psychosocial stimulation. If not addressed with proper nutrition, it can lead to reduced child growth. According to the Indonesian Ministry of Health, stunting is influenced by several factors, including maternal, infant, and toddler factors, as well as social, economic, and environmental conditions. According to Global Nutrition, by 2025, it is estimated that children aged ≤ 5 years will experience stunting, with an increase of 171-314 million individuals worldwide, with 90% originating from countries in Africa and Asia. The province of Lampung has shown improvement, with a stunting prevalence of 15.2% in 2022, aiming to reach the national target of around 14%. Based on nutritional status monitoring in 2017, the prevalence of stunting was 35.20%, and according to the Indonesia Nutrition Status Study (INSS) and Community-Based Nutrition Recording and Reporting (CBNRP), the prevalence of stunting in Pesawaran in 2022 was 3.50%.Purpose: To determine the impact of using the 5J Pregnancy Nutrition Guidebook in educating pregnant mothers about preventing fetal growth restriction on the knowledge, attitudes, and behaviors of mothers in the working area of Gedong Tataan Community Health Center, Pesawaran, Lampung.Method: This quantitative research employed an analytical survey design with a quasi-experimental one-group pretest-posttest method. The dependent variables in this study were the level of knowledge, attitude, and behavior of mothers, while the independent variable was education using the 5J guidebook. The research was conducted in the Gedong Tataan Community Health Center, Pesawaran, Lampung in August 2023 with a sample size of 30 using total sampling technique, and a paired sample t-test was performed.Results: Knowledge improved by 2.37 points after receiving education, with an increase difference of 1.24, and the Wilcoxon statistical test yielded a p-value of 0.000 (<0.05). Respondents' attitudes increased by 1.93 points after receiving education, although this value was in the low range, it saw a rise with a difference of 0.9, and the p-value was 0.000 (<0.05). Behavior after receiving education increased to 1.23 with an increase difference of 0.2, and the Wilcoxon statistical test showed an improvement with a p-value of 0.000 (<0.05). The test results indicate the influence of education using the 5J guidebook on maternal knowledge, attitude, and behavior.Conclusion: Educational media using the 5J guidebook has a significant influence on maternal knowledge, attitude, and behavior regarding nutrition management in the prevention of stunting.